The role of stony soils in hillslope and catchment runoff formation - Mujtaba, Babar (2020)
The role of stony soils in runoff response of mountain catchments is rarely studied. We have compared simu-lated response of stony soils with measured catchment runoff for events caused by rains of small and high intensities in the mountain catchment of the Jalovecký Creek, Slovakia. The soil water response was simulated for three sites with stoniness 10–65% using the Hydrus-2D single porosity model. Soil hydraulic parameters employed in the modelling, i. e. the saturated hydraulic conductivity and parameters of the soil water retention curves, were obtained by two approaches, namely by the Representative Elementary Volume approach (REVa) and by the inverse modelling with Hydrus-1D model (IMa). The soil water outflow hydrographs simulated by Hydrus-2D were compared to catchment runoff hydro-graphs by analysing their skewness and peak times. Measured catchment runoff hydrographs were similar to simulated soil water outflow hydrographs for about a half of rainfall events. Interestingly, most of them were caused by rainfalls with small intensity (below 2.5 mm/10 min). The REV approach to derive soil hydraulic parameters for soil water out-flow modelling provided more realistic shapes of soil water outflow hydrographs and peak times than the IMa approach.